Criminal Liability Against Child Exploitation Perpetrators by Educators in Islamic Boarding Schools - Amri, Ahmad Ihsan (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2022)
The children exploitation that occurs within the scope of Islamic boarding schools is increasing and it is required for strict supervision from the government to take preventive measures against this crime even though the implementation of Islamic boarding schools that regulated in Law of the Republic Indonesia No. 18/2019 concerning Islamic Boarding Schools. The aims of this research is divided into two types, to examine the effectiveness of positive law in Indonesia in law enforcement cases of crimes against children as victims and examine the legal sanctions from the actions of educators who exploit children in the Islamic boarding school environment; also, to fulfillment of academic requirements of researcher to complete the task of child criminal course at the Postgraduate of Law Faculty in Narotama University Surabaya and add theoretical and practical knowledge in legal science, especially in criminal law. The method used is juridical-normative method combined with conceptual, statutory and case approach. The source data of this research consist of primary, secondary, and tertiary legal materials. In addition, the data collection used library research. The criminal sanctions for perpetrators of child exploitation in Islamic boarding schools are regulated in the Child Protection Law in Article 761 and Article 88 which the perpetrator is threatened with a maximum imprisonment of 10 years and a maximum fine of IDR 200,000,000,- and the child as a victim can apply for restitution rights or compensation based on Government Regulation No. 43/2017 concerning the Implementation of Restitution for children who are victims of criminal acts.